Combined Effects of Thyroxine with Vitamin B12 on Electrophysiological Changes in Sensory Functions of Sural Nerve of Newly Diagnosed Hypothyroid Female Patients - Ahmed, Farjana; Chowdhury, Md Arifuzzaman; Banik, Shyamal Chandra; Sultana, Nayma; Towhid, Ferdous (KYAMC Journal, 2022)
Background: Combination of thyroxine with vitamin B12 can improve the electrophysiological status of sensory function of sural nerve in newly diagnosed hypothyroid patients. Objectives: To observe the combined effects of thyroxine with vitamin B12 on electrophysiological changes in sensory function of sural nerve of newly diagnosed hypothyroid female. Materials and Methods: This prospective interventional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) between July’ 2015 to June’ 2016 on 40 newly diagnosed hypothyroid female patients. Among them, 20 hypothyroid patients received only thyroxine (HT-T4) and another 20 hypothyroid patients received combined therapy of thyroxine with vitamin B12 (HT-C) for 90 consecutive days. Nerve conduction parameters of sensory functions of sural nerve were studied to observe the electrophysiological status and vitamin B12 level was also estimated to observe its level by using standard method. The statistical analysis was done by ANOVA test, paired, independent sample ‘t’ test and Chi-square (χ2) test. Results: In this study, latency was significantly decreased, amplitude and NCV were significantly increased in sensory functions of sural nerve of hypothyroid patients after 90 days supplementation of combined therapy of thyroxine with vitamin B12 in comparison to those of their pre-supplemented state and also to those of patients with only thyroxine treatment. Conclusion: The present study revealed the combination of thyroxine with vitamin B12 can reduce the symptoms of hypothyroid and accelerate the nerve conduction velocity of sensory functions of sural nerve more efficiently than the treatment with thyroxine alone. KYAMC Journal. 2022;12(04): 208-212